Corporate Governance and Corporate Social Responsibility on Financial Performance in Manufacturing Companies at The Indonesian Stock Exchange - Idrus, Arifin (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of corporate governance and social responsibility on financial performance in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The population in this study was 18 companies obtained using a purposive sampling method in automotive sub-sector manufacturing companies during the 2020-2022 period and based on predetermined criteria, a sample of 14 manufacturing companies listed on the Indonesia Stock Exchange was obtained. The total sample data for the 2020-2022 period is 42 samples. The analysis method used is multiple linear analysis with the help of SPSS software. The research results show that governance and corporate social responsibility have a positive and significant influence on the financial performance of manufacturing companies listed on the Indonesian Stock Exchange in 2020